Long-term quality of life and functional outcomes in adults surgically treated for intramedullary spinal cord tumor - Tufo, Tommaso; Grande, Eleonora; Bevacqua, Giuseppina; Di Muccio, Ines; Cioni, Beatrice; Meglio, Mario; Ciavarro, Marco (Frontiers in Psychology, 2023)
Introduction: Intramedullary spinal cord tumors (IMSCTs) are rare but clinically significant entities that may cause severe neurological decline with progressive pain and motor or sensory deterioration. Besides the beneficial effects of surgical treatment and the long-term progression-free survival, neurological deficits may still persist after surgery and information about the long-term patients’ health-related quality of life (QoL) are still lacking. Here we investigate the patients’ health perception fifteen years after the surgery, in an overall patients' well-being framework. Methods: Patients surgically treated for IMSCT over a period from 1996 to 2011 were selected. After a mean of fifteen years from the surgery, patients self-administered questionnaire on disability, pain, sleep quality, and QoL were collected and neurological postoperative evaluation at chronic stage were reexamined. Results: Neurological deficits are reported in half of the patients in the postoperative chronic phase. Fifteen years post-surgery, half of the patients still report mild or severe disability grades, associated with significantly higher pain and poor sleep and QoL. In accordance, also the neurological condition measured at the chronic stage is significantly related not only to disease-specific symptoms (i.e., pain) but even to sleep quality complaints and poor QoL, measured at fifteen years follow-up. Conclusions: Health-related QoL is an important secondary outcome in patients. Although the progression-free survival, worse postoperative neurological conditions could predict long-term sequelae reflecting in patients’ poor health perception. It suggests the importance of preserving patients’ functional status and globally evaluating patients' well-being, to handle disease-specific symptoms but even more general aspects of QoL.